ENTREPRENEURSHIP EDUCATION IN TERTIARY INSTITUTIONS: A PARADIGM FOR SUSTAINABLE DEVELOPMENT - Victor O, Okoye; Chinasa R., Okoye (International Journal of Research -GRANTHAALAYAH, 2019)
The paper attempts to highlight the importance of entrepreneurship education in the quest for sustainable development and the role of tertiary institutions in promoting sound entrepreneurship education. In Nigeria, just like other developed and developing countries, tertiary institutions, through research and innovation, have been saddled with the responsibility of integrating sustainable development into their teachings and learnings. As societies look for solutions that could lead to sustainable development, entrepreneurship education, being offered in tertiary institutions, is becoming increasingly more appealing. Thus, given their primary role as knowledge producers, tertiary institutions, through research and innovation, can serve as powerful means to help create a more sustainable future by engaging in entrepreneurship education. Going forward, this paper also highlights the role of tertiary institutions in this very important subject of sustainable development, the reasons why people choose to be entrepreneurs as well as the importance of entrepreneurship education. The paper concludes by proffering suggestions on the way forward.